ARCA SARASWATI DARI NGANJUK - Peter Ferdinandus (Berkala Arkeologi, 1994)
The Oudheidkundige Dienst photo collection in Nederlandsch-India contains a bronze statue of Saraswati from Nganjuk. The statue is depicted with the attributes of a harp instrument with a relief of makara. If you look at the statue of Saraswati from Nganjuk, it clearly shows a statue of a goddess and not a musical instrument, even though the character of Dewi Saraswati is a harp instrument. In the context of Hinduism, the Saraswati statue is considered the embodiment of truth or the manifestation of the highest beauty and at the same time depicting the truth of religion and philosophy. Therefore, in this study the author does not only look at the musicology side but also from the archeology side, with the approach of texts related to Saraswati. The depiction of the statue of Saraswati from Nganjuk not only shows the depiction of Saraswati as the goddess of art but as a symbol of the goddess of water as well. Therefore, the statue of Saraswati from Nganjuk shows a symbol of worshiping the goddess Saraswati as the goddess of water and arts.